2022
DOI: 10.1177/10732748221132646
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices Towards Human Papillomavirus Vaccination Among Medical Doctors at a Tertiary Hospital: A Cross Sectional Study

Abstract: Background Human papillomavirus (HPV) infection is a common sexually transmitted disease, characterised by persistent infection with high-risk strains leading to malignant conditions such as cervical cancer. The HPV vaccine is a well-known primary preventive measure for HPV infections. Previous studies have shown that medical doctors’ vaccine recommendation is one of the key strategies in improving HPV vaccine uptake. In 2019, Zambia rolled out the free national HPV vaccination program targeting 14-year-old gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Our study corroborated the factors on HPVV uptake we had previously summarized in our review from across English Canada (Khan et al, 2023 ) in the context of SK. The study findings align with the literature that HPVV uptake is largely hindered by vaccine attitudes driven by either lack of awareness (Cartmell et al, 2018 ) information and literacy (Alhusayn et al, 2022 ; Fernandes et al, 2018 ) or its adequacy (Lubeya et al, 2022 ). The study adds to the literature by highlighting the context-specific barriers and facilitators to the uptake of HPVV at three different levels across SK in an attempt to provide views from multiple prescriptive.…”
Section: Discussionsupporting
confidence: 88%
“…Our study corroborated the factors on HPVV uptake we had previously summarized in our review from across English Canada (Khan et al, 2023 ) in the context of SK. The study findings align with the literature that HPVV uptake is largely hindered by vaccine attitudes driven by either lack of awareness (Cartmell et al, 2018 ) information and literacy (Alhusayn et al, 2022 ; Fernandes et al, 2018 ) or its adequacy (Lubeya et al, 2022 ). The study adds to the literature by highlighting the context-specific barriers and facilitators to the uptake of HPVV at three different levels across SK in an attempt to provide views from multiple prescriptive.…”
Section: Discussionsupporting
confidence: 88%
“…Healthcare provider (HCPs) recommendations are a significant factor that motivates the general population and parents to vaccinate their children against HPV [ 16 , 17 , 18 , 19 ]. Additionally, knowledge of HPV-related issues is a crucial predictor of HCP confidence and a willingness to recommend HPV vaccines [ 20 , 21 , 22 ]. Previous studies have also identified various factors that impact HCPs’ knowledge of HPV and HPV vaccines, including their profession, type of license, age, education level, and job title [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sixty-nine (65.3%) of the physicians in their survey study had more than 10 years of clinical experience. A total of 66 (54.6%) physicians recommended HPV vaccination ( 5 ). On the contrary, physicians were more likely to recommend the vaccine in our study.…”
Section: Discussionmentioning
confidence: 99%